FACILITIES LAYOUT PLANNING SOFTWARE DEVELOPMENT BY USINGSELF ADAPTIVE HARMONY SEARCH - SLICING TREE STRUCTURE ALGORITHM DEVELOPMENT AND DIJKSTRA - IRWAN SURYA (NIM : 13413027), EMMANUEL
Final year Industrial Engineering students of Institut Teknologi Bandung get the course material to be able to design the facility layout. The students apply the knowledge obtained in the Integrated System Design Practicum (PPST) IV. Students, as practitioners, by using Computerized Relative Allocation of Facilities Technique (CRAFT) and WinQSB software to design the layout. The author conducted a preliminary study of both software using 12 respondents. The outcoming result is practitioners cannot accept both software. In this study, author built a software by using NetBeans IDE 3.2 as software developer. The softwareÃ‚Â’s name is harmony memory layout planning (HMLP). The development process adapted the Framework for the Application of Systems Thinking (FAST) methodology. Software development was done by taking into considering shortcomings of the software previously used and the user requirements, which were obtained from interviews. The algorithm, which was used in this research, was developed by Napitupulu (2017), derived from Chang and Ku algorithm (2013) which was self-adaptive harmony search with quadratically constrained problem for slicing tree structure layout (SHS-QCP-STS). Dijkstra algorithm was also used in aisle development features. Tests were performed on HMLP software using black box testing, usability testing, and system usability scale (SUS). The test results showed that users accepted the software with an average SUS score of 70.42; while the average SUS score for CRAFT and WinQSB are 46.67 and 43.96 respectively. The average time spent by respondents solving the problem using HMLP, CRAFT, and WinQSB were 11'42", 20'10", and 22'28 "respectively.